Involvement of blood mononuclear cells in the infertility, age-associated diseases and cancer treatment - Bukovsky, Antonin (World journal of stem cells, 2016)
Blood mononuclear cells consist of T cells and monocyte derived cells. Beside immunity, the blood mononuclear cells belong to the complex tissue control system (TCS), where they exhibit morphostatic function by stimulating proliferation of tissue stem cells followed by cellular differentiation, that is stopped after attaining the proper functional stage, which differs among various tissue types. Therefore, the term immune and morphostatic system (IMS) should be implied. The TCS-mediated morphostasis also consists of vascular pericytes controlled by autonomic innervation, which is regulating the quantity of distinct tissues in vivo. Lack of proper differentiation of tissue cells by TCS causes either tissue underdevelopment, e.g., muscular dystrophy, or degenerative functional failures, e.g., type 1 diabetes and age-associated diseases. With the gradual IMS regression after 35 years of age the gonadal infertility develops, followed by a growing incidence of age-associated diseases and cancers. Without restoring an altered TCS function in a degenerative disease, the implantation of tissue-specific stem cells alone by regenerative medicine can not be successful. Transfused young blood could temporarily restore fertility to enable parenthood. The young blood could also temporarily alleviate aging diseases, and this can be extended by substances inducing IMS regeneration, like the honey bee propolis. The local and/or systemic use of honey bee propolis stopped hair and teeth loss, regressed varicose veins, improved altered hearing, and lowered high blood pressure and sugar levels. Complete regression of stage IV ovarian cancer with liver metastases after a simple elaborated immunotherapy is also reported.
Keywords: Infertility treatment; Tissue morphostasis; Transfusion morphostatic treatment; Age-associated diseases; Blood mononuclear cells; Stem cells; Tissue control system; Immune system; Regenerative medicine; Cancer immunotherapy